2019
DOI: 10.3122/jabfm.2019.03.180356
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Increased Hydrocodone Regulation on Opioid Prescribing in an Urban Safety-Net Health Care System

Abstract: Background: Hydrocodone-combination analgesics were changed from Schedule III to Schedule II to discourage the prescribing of these analgesics. Our primary aim was to explore the effect of hydrocodone rescheduling on opioid prescribing within an urban safety-net health care system.Methods and Design: Data were extracted from electronic records of ambulatory patients (N ‫؍‬ 82,432 patients) prescribed hydrocodone-combination, codeine-combination, or tramadol opioid analgesics (N ‫؍‬ 200,675 prescriptions) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The tramadol scheduling law is thus a unique case as it was first enacted at the state level and then at the federal level, in identical form. 3 Previous descriptive research suggests that federal up-scheduling of HCPs is associated with decreases in its prescribing (Jones et al, 2016;Bernhardt et al, 2016;Fleming et al, 2017;Gudin and Lee, 2013;Murimi et al, 2019;Northrup et al, 2019); a similar finding occurs in the first economic study of HCPs' up-scheduling (Beheshti, 2019), which finds improved labor market conditions in areas with baseline high intensity of HCP reliance. However, there is no study to date that examines the spillover hypothesis to the closest competitor, tramadol.…”
mentioning
confidence: 72%
“…The tramadol scheduling law is thus a unique case as it was first enacted at the state level and then at the federal level, in identical form. 3 Previous descriptive research suggests that federal up-scheduling of HCPs is associated with decreases in its prescribing (Jones et al, 2016;Bernhardt et al, 2016;Fleming et al, 2017;Gudin and Lee, 2013;Murimi et al, 2019;Northrup et al, 2019); a similar finding occurs in the first economic study of HCPs' up-scheduling (Beheshti, 2019), which finds improved labor market conditions in areas with baseline high intensity of HCP reliance. However, there is no study to date that examines the spillover hypothesis to the closest competitor, tramadol.…”
mentioning
confidence: 72%
“…One‐quarter of studies did not impose age restrictions (32 studies 23–53 ), while 83 studies included adults only, 11 studies 54–64 focused exclusively on the elderly (aged 65+ years) and two studies 65,66 focused on adolescents and young adults (13‐29 years old). Study populations varied substantially in size, ranging from 121 67 to 48 million people 68 .…”
Section: Resultsmentioning
confidence: 99%
“…However, substitution effects varied across studies. Eight studies observed an increase in prescribing codeine (Schultz et al 2016;Seago et al 2016;Bernhardt et al 2017;Kuschel and Mort 2017;Raji et al 2018;Shumway et al 2018;Liu et al 2019;Northrup et al 2019) and tramadol (Schultz et al 2016;Seago et al 2016;Bernhardt et al 2017;Northrup et al 2019), while 6 studies found no significant changes in codeine (Chumpitazi et al 2017) or tramadol prescribing (Kuo et al 2018;Raji et al 2018;Shumway et al 2018;Liu et al 2019). Only 2 studies reported increased prescribing of oxycodone (Bernhardt et al 2017;Kuschel and Mort 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since the rescheduling of hydrocodone in 2014, several studies have evaluated the impact of the regulation on hydrocodone prescribing (Usmani et al 2020). Most of these studies, focused on physicians, reported a substantial reduction in hydrocodone prescriptions after the regulation took effect in 2014 (Jones et al 2016; Oehler et al 2016; Schultz et al 2016; Seago et al 2016; Bernhardt et al 2017; Chumpitazi et al 2017; Kuschel and Mort 2017; Tran et al 2017; Kuo et al 2018; Raji et al 2018; Shumway et al 2018; Liu et al 2019; Northrup et al 2019; Usmani et al 2020). However, substitution effects varied across studies.…”
Section: Discussionmentioning
confidence: 99%